Mitochondrial Complex IV Subunit 4 Isoform 2 Is Essential for Acute Pulmonary Oxygen Sensing. Issue 4 (4th August 2017) - Sommer, Natascha; Hüttemann, Maik; Pak, Oleg; Scheibe, Susan; Knoepp, Fenja; Sinkler, Christopher; Malczyk, Monika; Gierhardt, Mareike; Esfandiary, Azadeh; Kraut, Simone; Jonas, Felix; Veith, Christine; et al.
Abstract : Rationale: : Acute pulmonary oxygen sensing is essential to avoid life-threatening hypoxemia via hypoxic pulmonary vasoconstriction (HPV) which matches perfusion to ventilation. Hypoxia-induced mitochondrial superoxide release has been suggested as a critical step in the signaling pathway underlying HPV. However, the identity of the primary oxygen sensor and the mechanism of superoxide release in acute hypoxia, as well as its relevance for chronic pulmonary oxygen sensing, remain unresolved. Objectives: : To investigate the role of the pulmonary-specific isoform 2 of subunit 4 of the mitochondrial complex IV (Cox4i2) and the subsequent mediators superoxide and hydrogen peroxide for pulmonary oxygen sensing and signaling. Methods and Results: : Isolated ventilated and perfused lungs from Cox4i2 −/− mice lacked acute HPV. In parallel, pulmonary arterial smooth muscle cells (PASMCs) from Cox4i2 −/− mice showed no hypoxia-induced increase of intracellular calcium. Hypoxia-induced superoxide release which was detected by electron spin resonance spectroscopy in wild-type PASMCs was absent in Cox4i2 −/− PASMCs and was dependent on cysteine residues of Cox4i2. HPV could be inhibited by mitochondrial superoxide inhibitors proving the functional relevance of superoxide release for HPV. Mitochondrial hyperpolarization, which can promote mitochondrial superoxide release, was detected during acute hypoxia in wild-type but not Cox4i2 −/− PASMCs. Downstream signaling determined by patch-clamp measurements showed decreased hypoxia-induced cellular membrane depolarization in Cox4i2 −/− PASMCs compared with wild-type PASMCs, which could be normalized by the application of hydrogen peroxide. In contrast, chronic hypoxia-induced pulmonary hypertension and pulmonary vascular remodeling were not or only slightly affected by Cox4i2 deficiency, respectively. Conclusions: : Cox4i2 is essential for acute but not chronic pulmonary oxygen sensing by triggering mitochondrial hyperpolarization and release of mitochondrial superoxide which, after conversion to hydrogen peroxide, contributes to cellular membrane depolarization and HPV. These findings provide a new model for oxygen-sensing processes in the lung and possibly also in other organs. Abstract : Supplemental Digital Content is available in the text.